2018
DOI: 10.1021/acs.jpcc.8b01978
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Mushroom Nanoantenna for Fluorescence Enhancement by Matching the Stokes Shift of the Emitter

Abstract: Nanoantenna-enhanced fluorescence is a promising method in many emergent applications, such as single molecule detection. The excitation and emission wavelengths of emitters can be well separated depending on the corresponding Stokes shifts, preventing optimal fluorescence enhancement by a rudimentary nanoantenna. We illustrate a hybrid mushroom nanoantenna that can achieve overall enhancements (e.g., excitation rate, quantum yield, fluorescence enhancement) in fluorescence emission. The nanoantenna is made of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…[292] In ref. [293], a hybrid mushroom-shaped nanoantenna was designed to achieve high excitation rates, quantum yields, and fluorescence enhancements. The nanostructure consisted of a plasmonic metal stripe and a dielectric cap.…”
Section: Increasing Purcell Factor and Collection Efficiencymentioning
confidence: 99%
“…[292] In ref. [293], a hybrid mushroom-shaped nanoantenna was designed to achieve high excitation rates, quantum yields, and fluorescence enhancements. The nanostructure consisted of a plasmonic metal stripe and a dielectric cap.…”
Section: Increasing Purcell Factor and Collection Efficiencymentioning
confidence: 99%
“…c) Reproduced with permission. [ 51,104 ] Copyright 2018, 2019, American Chemical Society. d) Reproduced under the terms of Creative Commons Attribution 4.0 Public License.…”
Section: Recent Progress In Nanoantenna‐enhanced Ledmentioning
confidence: 99%
“…[ 103 ] The silicon nanorod is mainly responsible for redirecting the emission from the plasmonic‐enhanced dipole radiation to the forward direction. Other novel structures, like hybrid mushroom and metal nanodisk–dielectric nanoring proposed by Sun et al., [ 51,104 ] are shown in Figure 6c. They found that when the plasmon mode of the metal constituent resonates strongly with the magnetic dipole mode of the dielectric constituent, the excitation field was greatly improved and the outgoing light is directed in the vertical direction.…”
Section: Recent Progress In Nanoantenna‐enhanced Ledmentioning
confidence: 99%
“…Non-radiative relaxation from the excited state reduces the fluorescence quantum yields of molecular probes used in fluorescence experiments, which affects the maximum rate at which information is obtained by detected photons. Amelioration comes from advances being made with techniques such as near-field scanning optical microscopes [ 6 , 7 ], the use of nanostructures such as nano-antennas [ 8 , 9 , 10 , 11 , 12 , 13 ], and zero-mode waveguides (ZMW) [ 14 ]. Nano-antennas and zero-mode waveguides enhance fluoresence by creating a surface plasmon resonance that is confined to an active region within the nanostructure.…”
Section: Introductionmentioning
confidence: 99%